Biologically Aggressive Phenotype and Anti-cancer Immunity Counterbalance in Breast Cancer with High Mutation Rate - Hideo Takahashi (Nature Portfolio, 2020)
Abstract While cancer cells gain aggressiveness by mutations, abundant mutations release neoantigens, attracting anti-cancer immune cells. We hypothesized that in breast cancer (BC), where mutation is less common, tumors with high mutation rates demonstrate aggressive phenotypes and attract immune cells simultaneously. High mutation rates were defined as the top 10% of the mutation rate, utilizing TCGA and METABRIC transcriptomic data. Mutation rate did not impact survival although high mutation BCs were associated with aggressive clinical features, such as more frequent in ER-negative tumors (p < 0.01), in triple-negative subtype (p = 0.03), and increased MKI-67 mRNA expression (p < 0.01) in both cohorts. Tumors with high mutation rates were associated with APOBEC3B and homologous recombination deficiency, increasing neoantigen loads (all p < 0.01). Cell proliferation and immune activity pathways were enriched in BCs with high mutation rates. Furthermore, there were higher lymphocytes and M1 macrophage infiltration in high mutation BCs. Additionally, T-cell receptor diversity, cytolytic activity score (CYT), and T-cell exhaustion marker expression were significantly elevated in BCs with high mutation rates (all p < 0.01), indicating strong immunogenicity. In conclusion, enhanced immunity due to neoantigens can be one of possible forces to counterbalance aggressiveness of a high mutation rate, resulting in similar survival rates to low mutation BCs.